PTF10ops-a subluminous, normal-width light curve Type Ia supernova in the middle of nowhere - Maguire, K; Sullivan, M; Thomas, R; Nugent, P; Howell, D; Gal-Yam, A; Arcavi, I; Ben-Ami, S; Blake, S; Botyanszki, J; Buton, C; Cooke, J; et al. (2011)
PTF10ops is a Type Ia supernova (SN Ia), whose light curve and spectral properties place it outside the current SN Ia subtype classifications. Its spectra display the characteristic lines of subluminous SNe Ia, but it has a normal-width light curve with a long rise time, typical of normal-luminosity SNe Ia. The early-time optical spectra of PTF10ops were modelled using a spectral fitting code and found to have all the lines typically seen in subluminous SNe Ia, without the need to invoke more uncommon elements. The host galaxy environment of PTF10ops is also unusual with no galaxy detected at the position of the SN down to an absolute limiting magnitude of r≥-12.0mag, but a very massive galaxy is present at a separation of ∼148kpc and at the same redshift as suggested by the SN spectral features. The progenitor of PTF10ops is most likely a very old star, possibly in a low-metallicity environment, which affects its explosion mechanism and observational characteristics. PTF10ops does not easily fit into any of the current models of either subluminous or normal SN Ia progenitor channels. © 2011 The Authors Monthly Notices of the Royal Astronomical Society © 2011 RAS.